PENERAPAN MODEL PEMBELAJARAN KOOFERATIF TIPE NHT (NUMBERED HEADS TOGETHER) UNTUK MENINGKATKAN PEMAHAMAN SUGGESTION AND OFFER PADA SISWA KELAS XI IPS 2 SMA NEGERI 7 DENPASAR TAHUN PELAJARAN 2018/2019 - Karba, I Ketut (LP2M IKIP PGRI Bali, 2019)
This study aims to improve Suggestion and Offer capabilities and improve student responses in Suggestion and Offer teaching and learning by applying the Numbered Heads Together (NHT) type of cooperative learning model. This class research was conducted in class XI IPS 2 Denpasar Public High School 7 Academic Year 2018/2019 which was located at No. Cambodia Street. 9 Denpasar. The subjects of this class action research were students of class XI IPS 2 in Public High School 7 Denpasar in 2018/2019 Academic Year, amounting to 36 students, consisting of 15 female students and 21 male students and the object of research was the application of the Numbered Heads type of cooperative learning model Together (NHT). In this study a set of data collection methods are used, namely test methods and observation methods. This research will be carried out in several cycles, each of which consists of four stages, namely (1) planning, (2) implementation of actions, (3) observation, and (4) reflection.         The results showed that (1) The application of the Numbered Heads Together (NHT) type of cooperative learning model can improve students' Suggestion and Offer comprehension skills. (2) The application of the Numbered Heads Together (NHT) type of cooperative learning model can improve the responses of students of class XI IPS 2 in Denpasar Public High School 2018/2019 in learning the ability to understand Suggestion and Offer material.